Psychometric evaluation of the Questionnaire about the Process of Recovery (QPR). (December 2015) - Williams, Julie; Leamy, Mary; Pesola, Francesca; Bird, Victoria; Boutillier, Clair Le; Slade, Mike
Abstract : Background: Supporting recovery is the aim of national mental health policy in many countries. However, only one measure of recovery has been developed in England: the Questionnaire about the Process of Recovery (QPR), which measures recovery from the perspective of adult mental health service users with a psychosis diagnosis. Aims: To independently evaluate the psychometric properties of the 15- and 22-item versions of the QPR. Method: Two samples were used: data-set 1 ( n = 88) involved assessment of the QPR at baseline, 2 weeks and 3 months. Data-set 2 ( n = 399; trial registration: ISRCTN02507940) involved assessment of the QPR at baseline and 1 year. Results: For the 15-item version, internal consistency was 0.89, convergent validity was 0.73, test–retest reliability was 0.74 and sensitivity to change was 0.40. Confirmatory factor analysis showed the 15-item version offered a good fit. For the 22-item version, the interpersonal subscale was found to underperform and the intrapersonal subscale overlaps substantially with the 15-item version. Conclusions: Both the 15-item and the intrapersonal subscale of the 22-item versions of the QPR demonstrated satisfactory psychometric properties. The 15-item version is slightly more robust and also less burdensome, so it can be recommended for use in research and clinical practice.